2016
DOI: 10.1186/s13567-016-0312-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental caprine neosporosis: the influence of gestational stage on the outcome of infection

Abstract: Here, we assessed outcome of experimental infection by Neospora caninum in goats intravenously inoculated with 106 tachyzoites of the Nc-Spain7 isolate at 40 (G1), 90 (G2) and 120 (G3) days of gestation. Infected goats had fever between 5 and 9 days post inoculation (dpi); all were seropositive at the time of abortion/birth. Foetal death occurred in G1 from 10 to 21 dpi (n = 7) and in G2 from 27 to 35 dpi (n = 4). Goats in G2 also had seropositive stillbirth (n = 1) and healthy kids (n = 2). G3 goats (n = 7) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
1
24
2
3
Order By: Relevance
“…However, these lesions differ in intensity from those presented here, since they were described as mild lesions (Porto et al 2016). The differences in the intensity of these placental lesions could be due to differences regarding the N. caninum strains, since Porto et al (2016) used a strain derived from cattle in Spain, and the goats from the present study were naturally infected with strains circulating in Brazil. In addition, the inoculation route and number of inoculated parasites may explain the differences regarding placental lesions observed in the present study and those reported by Porto et al (2016).…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…However, these lesions differ in intensity from those presented here, since they were described as mild lesions (Porto et al 2016). The differences in the intensity of these placental lesions could be due to differences regarding the N. caninum strains, since Porto et al (2016) used a strain derived from cattle in Spain, and the goats from the present study were naturally infected with strains circulating in Brazil. In addition, the inoculation route and number of inoculated parasites may explain the differences regarding placental lesions observed in the present study and those reported by Porto et al (2016).…”
Section: Discussioncontrasting
confidence: 80%
“…Similarly, non-purulent necrotic placentitis was described in goats experimentally infected (Porto et al 2016). However, these lesions differ in intensity from those presented here, since they were described as mild lesions (Porto et al 2016).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations